Pengaruh Pendekatan Cognitive Behavior Therapy (CBT) terhadap Perilaku Inhalen “Ngelem” pada Remaja di Kecamatan Kambu Kota Kendari - Nurfantri, Nurfantri (Health Information : Jurnal Penelitian, 2021)
Adolescence is a period of transition from childhood to adulthood. This period goes through puberty which is full of storms and stress, the tendency to engage in risky behavior. If this stage is not passed well or fails, it may lead to a period of crisis, which is marked by a tendency to appear deviant behavior. including the use of narcotics and glue (inhalants). This glue is used by inhalation of aibon glue or with other types of glue. To reduce the tendency of deviant behavior in adolescents, the alternative given is intervention through Cognitive Behavior Therapy (CBT) approach. The purpose of this study to determined the effect of giving CBT on the behavior of the inhaled “ngelem” in adolescents in Kambu District, Kendari City. This study was a non-randomized experiment in one group with pre-posttest and follow-up. CBT was divided into 4 sessions, each session carried out 1-2 times a week. The pre-posttest used an inherent substance abuse assessment instrument and behavioral observation sheet. Based on statistical analysis using the paired sample t-test method, there was a significant difference between before and after CBT with p-values ??of 0.02 (evaluation week I) and 0.008 (evaluation week II). CBT can be used to help teens control their inhaled “ngelem” behavior.